P50 Up-regulated circPOLD1 promotes tumorigenesis in cervical cancer. (1st November 2019) - Zhao, L; Zhang, Y; Lv, W; Cheng, X; Xie, X
Abstract : Introduction/Background: The role of circular RNAs (circRNAs) still need to be explored in cancers. We aimed to investigate differentially expressed circRNAs in onconegic progress of cervical cancer, and focus on one of them to verify its effects on the development in cervical cancer. Methodology: High-throughput sequencing technique was performed to identify circRNAs expression profiles in cervical tissues of normal, High Squamous Intraepithelial Lesion(HSIL), and squamous-cell carcinoma (SCC)(each n=6). The results were validated by quantitative real-time PCR (qPCR) in 69 samples. The effect of circRNAs on proliferation, clonal formation and apoptosis were observed in cervical cancer cells by circRNA knockdown. RNA pulldown assay and RNA Binding Protein Immunoprecipitation Assay (RIP) was used to verify the combination between circRNA and its potential RNA binding protein, based on the bioinformatics prediction program. Results: Totally 798 differentially expressed circRNAs with more than 2-fold change were identified(P<0.05), of those, 2 down-regulated and 6 up-regulated ones were validated by qPCR. CircPOLD1 was selected to further investigate the function. Functional assays indicated that of circPOLD1 knockdown inhibited cellular proliferation and induced apoptosis in cervical cancer cells. The bioinformatics prediction program predicted several RNA binding proteins including Y-box binding protein-1 (YB1), an oncogene that has been widely researched, that could have bind with circPOLD1. The circPOLD1 directly bound to YBX1 and inhibited its function. Same as circPOLD1, knockdown of YB1 could inhibite cellular proliferation and apoptosis in cervical cancer cells. Conclusion: CircPOLD1 may play an oncogenic role on cervical cancer tumorigenesis by targeting YBX1. Disclosure: Nothing to disclose.